Reconfiguring the public and the private: Noc-Noc arts festival, Guimarães, Portugal - Sarmento, João (2018)
In the past decades many cities have experienced growing pressure to produce and stage cultural events of different sorts to promote themselves and improve economic development. Culture-led development often relies on significant public investment and major private-sector sponsoring. In the context of strained public finances and profound economic crisis in European peripheral countries, local community low-budget events that manage to create significant fluxes of visitors and visibility assume a particular relevance. This paper looks at the four editions (2011–2014) of Noc-Noc, an arts festival organized by a local association in the city of Guimarães, Portugal, which is based on creating transient spaces of culture by transforming numerous homes, commercial outlets and other buildings into ephemeral convivial and playful ‘public’ environments. By interviewing a sample of people who have hosted (sometimes doubling as artists) these transitory art performances and exhibitions, artists and the events’ organizers and by experiencing the four editions of the event and engaging in multiple informal conversations with the public, this paper attempts to discuss how urban citizens may disrupt the cleavages between public and private space permitting various transgressions, and unsettling the hegemonic condition of the city council as the patron of the large majority of events.